Downstreaming of Cassava into Functional Foods Based on Analog Rice in Sukoharjo Village, Ngaglik District, Sleman Regency, Yogyakarta - Ichlasia Ainul Fitri; Nafida Hetty Marhaeni; Saptya Fajar Pertiwi; Agus Setiyoko (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Indonesia is one of the countries with a high consumption of rice-based paddy, where rice has a high glycemic index. The Women Farmers Group (KWT Ngudi Makmur) in the Sukoharjo Village area, Ngaglik, Sleman, Yogyakarta as a partner has started producing various local agricultural products such as bananas and cassava into flour. Based on observations, partners have an experienced of declined in production and sales as a result of the pandemic situation, and there is still a lack of diversification of food based on local ingredients due to difficulties in carrying out other innovations in food processing. This also increases the number of unemployed and reduces community empowerment. The mentoring step is carried out with the observation stage, providing counseling and training to all KWT members in making various healthy food preparations based on local agriculture, inviting partners to re-examine the production process and record the components of raw materials, tools, labor, packaging until they are ready for market. The production process flow is examined jointly by the service team and partners. The results obtained show that partners are able to apply each stage of making analog rice. In the meantime, a product sensory test has been carried out by KWT members and several members of the public and the product results are acceptable.